2007
DOI: 10.1073/pnas.0607296104
|View full text |Cite
|
Sign up to set email alerts
|

The Aryl hydrocarbon receptor is activated by modified low-density lipoprotein

Abstract: Endogenous activation of the aryl hydrocarbon receptor (AHR) is required for normal vascular development. This biology led us to investigate the interplay between the AHR and vascular physiology by using an in vitro model of fluid shear stress. Using this system, we show that fluid flow induces a robust AHR-mediated increase in CYP1 expression. Furthermore, we demonstrate that incubation with sheared bovine or human sera is sufficient for AHR activation, indicating that direct cellular exposure to shear stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
90
0
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(102 citation statements)
references
References 40 publications
5
90
0
4
Order By: Relevance
“…In this regard, it is interesting to note that the invertebrate Ahr, specifically in Caenorhabditis elegans and Drosophila, does not seem to mediate response to xenobiotics but is rather at least partially implicated in determining neuronal fate and migration, which is in line with our observations (Crews and Brenman, 2006;Qin et al, 2006;Wernet et al, 2006;McMillan and Bradfield, 2007). Studies of rodent AhR lead to a more balanced view of its functions (McMillan and Bradfield, 2007). Indeed, although AhR knockout mice exhibit developmental defects, these defects are not evidently due to a lack of epithelial to mesenchymal transition.…”
Section: Discussionsupporting
confidence: 79%
“…In this regard, it is interesting to note that the invertebrate Ahr, specifically in Caenorhabditis elegans and Drosophila, does not seem to mediate response to xenobiotics but is rather at least partially implicated in determining neuronal fate and migration, which is in line with our observations (Crews and Brenman, 2006;Qin et al, 2006;Wernet et al, 2006;McMillan and Bradfield, 2007). Studies of rodent AhR lead to a more balanced view of its functions (McMillan and Bradfield, 2007). Indeed, although AhR knockout mice exhibit developmental defects, these defects are not evidently due to a lack of epithelial to mesenchymal transition.…”
Section: Discussionsupporting
confidence: 79%
“…Furthermore, the present investigation offers a relatively straightforward explanation for the reported ability of numerous structurally diverse chemicals to activate the AHR; such reports have been used to argue that the AHR binds ligands promiscuously (37). Our results also may explain why the addition of fresh Trp-containing medium to cell cultures (42), oxidative stress [e.g., by hyperoxia (43)], and hydrodynamic shear that gives rise to oxidized LDL (44,45), as well as why the addition of various complex mixtures, such as extracts of paper and ink, can activate the AHR (46,47).…”
Section: Discussionsupporting
confidence: 49%
“…Results from a variety of laboratories over the past decade have revealed that the AHR has key roles in the development of cardiovascular, reproductive, and neural systems as well as in hematopoiesis and regulation of immune responses (Benedict, Lin, Loeffler, Peterson, & Flaws, 2000; Esser & Rannug, 2015; Gasiewicz, Singh, & Bennett, 2014; Kimura, Ding, & Tohyama, 2016; Lahvis et al., 2005; Quintana & Sherr, 2013; Singh et al., 2014; Stockinger, Di Meglio, Gialitakis, & Duarte, 2014). Some of these functions may involve natural or endogenous ligands such as metabolites generated by the microbiome, tryptophan metabolites, or lipid‐derived molecules (Bessede et al., 2014; Hubbard, Murray, & Perdew, 2015; McMillan & Bradfield, 2007; Moura‐Alves et al., 2014). The exact relationship between the AHR‐dependent toxicity of DLCs and PAHs and these physiological roles of AHR is not yet clear.…”
Section: Ahr Pathwaymentioning
confidence: 99%